Effect of IMB Model Combined with Spousal Support Breastfeeding Intervention on PBSES Score and Breastfeeding Rate of Primipara with Chronic Hepatitis B Virus Infection. (15th September 2022) - Chen, Shaoping; Li, Linxian; Sun, Qianwen; Chen, Shulan; Cheng, Jing; Xiong, Siqi
Abstract : Objective . To analyze the effects of the info-motivation-behavior skills (IMB) model combined with spousal support breastfeeding intervention on breastfeeding Self-Efficacy Scale (PBSES) scores and breastfeeding rate of primiparas with chronic hepatitis B virus (HBV) infection. Methods . Seventy-four first-term pregnant women and 74 of their spouses were selected as the traditional control group by the convenience sampling method from July to September 2021 in obstetrics department of Shenzhen Third People's Hospital. 74 pregnant women with their first child and 74 spouses who had their first child checked during October to December 2021 were classified as the IMB model group. The traditional control group was applied with conventional intervention management mode, and the IMB model group was applied with intervention management mode based on IMB theory on the basis of the traditional control group. The self-efficacy scores of breastfeeding before and after intervention during pregnancy and during hospitalization were compared between the two groups, and the self-efficacy scores of paternal support for breastfeeding were compared. The exclusive breastfeeding rate of infants within 6 months and the maternal breastfeeding knowledge level of the two groups were compared, and the correlation between maternal breastfeeding self-efficacy score and feeding knowledge level was analyzed. Results . After pregnancy intervention, PBSES and FBSES-SF scores were significantly increased in both groups, and scores of scales in the IMB model group increased significantly than the traditional control group (all P < 0.05 ). The BSES-SF and FBSES-SF scores of the IMB model group increased significantly than the traditional control group at 3 days after delivery and at discharge (P < 0.05 ), and the scores of each scale at discharge in both groups increased significantly than those at 3 days after delivery (P < 0.05 ). The rate of exclusive breastfeeding in the IMB model group was 94.59% (70/74), and that in the traditional control group was 78.38% (58/74). There was a significant difference (χ 2 = 8.325, P = 0.004 ). At discharge, the score of maternal breastfeeding knowledge increased significantly in both groups, and the score of the IMB model group increased significantly than that of the traditional control group (all P < 0.05 ). Pearson correlation coefficient was used to analyze the correlation between PBSES score, FBSES-SF score, and maternal feeding knowledge level, which showed positive correlation (all P < 0.05 ). Conclusion . The self-efficacy of prenatal breastfeeding in pregnant women with HBV is low, and the application of the IMB model combined with the intervention mode of spy-supported breastfeeding has positive effects on the improvement of maternal breastfeeding efficiency, breastfeeding health knowledge level, and postpartum breastfeeding rate, which is worthy of clinical promotion and application.